Replicative senescence-associated gene expression changes in mesenchymal stromal cells are similar under different culture conditions - Schallmoser, Katharina; Bartmann, Christina; Rohde, Eva; Bork, Simone; Guelly, Christian; Obenauf, Anna C.; Reinisch, Andreas; Horn, Patrick; Ho, Anthony Dick; Strunk, Dirk; Wagner, Wolfgang (Haematologica, the hematology journal, 2010)
Background Research on mesenchymal stromal cells has created high expectations for a variety of therapeutic applications. Extensive propagation to yield enough mesenchymal stromal cells for therapy may result in replicative senescence and thus hamper long-term functionality in vivo. Highly variable proliferation rates of mesenchymal stromal cells in the course of long-term expansions under varying culture conditions may already indicate different propensity for cellular senescence. We hypothesized that senescence-associated regulated genes differ in mesenchymal stromal cells propagated under different culture conditions.Design and Methods Human bone marrow-derived mesenchymal stromal cells were cultured either by serial passaging or by a two-step protocol in three different growth conditions. Culture media were supplemented with either fetal bovine serum in varying concentrations or pooled human platelet lysate.Results All mesenchymal stromal cell preparations revealed significant gene expression changes upon long-term culture. Especially genes involved in cell differentiation, apoptosis and cell death were up-regulated, whereas genes involved in mitosis and proliferation were down-regulated. Furthermore, overlapping senescence-associated gene expression changes were found in all mesenchymal stromal cell preparations.Conclusions Long-term cell growth induced similar gene expression changes in mesenchymal stromal cells independently of isolation and expansion conditions. In advance of therapeutic application, this panel of genes might offer a feasible approach to assessing mesenchymal stromal cell quality with regard to the state of replicative senescence.